1992
DOI: 10.1083/jcb.117.6.1331
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface phosphatidylinositol-anchored heparan sulfate proteoglycan initiates mouse melanoma cell adhesion to a fibronectin-derived, heparin-binding synthetic peptide

Abstract: Abstract. Cell surface heparan sulfate proteoglycan (HSPG) from metastatic mouse melanoma cells initiates cell adhesion to the synthetic peptide FN-C/H II, a heparin-binding peptide from the 33-kD A chain-derived fragment of fibronectin. Mouse melanoma cell adhesion to FN-C/H II was sensitive to soluble heparin and pretreatment of mouse melanoma cells with heparitinase. In contrast, cell adhesion to the fibronectin synthetic peptide CS1 is mediated through an ot4B1 integrin and was resistant to heparin or hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…The present study findings, which showed that addition of heparan sulfate or treatment of the cell surface of SC with heparitinase reduced adhesion of SC onto EDA+ FN, suggest that heparan sulfate proteoglycans are responsible for the adhesion of (30). Furthermore, adhesion of murine melanoma cells or of human embryo fibroblasts onto the HepZderived peptide was inhibited by the addition of heparin or the treatment of cells with heparitinase (31).…”
Section: Discussionsupporting
confidence: 52%
“…The present study findings, which showed that addition of heparan sulfate or treatment of the cell surface of SC with heparitinase reduced adhesion of SC onto EDA+ FN, suggest that heparan sulfate proteoglycans are responsible for the adhesion of (30). Furthermore, adhesion of murine melanoma cells or of human embryo fibroblasts onto the HepZderived peptide was inhibited by the addition of heparin or the treatment of cells with heparitinase (31).…”
Section: Discussionsupporting
confidence: 52%
“…A second class of molecules capable of mediating cellmatrix interactions is the cell surface heparan sulfate and chondroitin sulfate PGs. Cell surface heparan sulfate and chondroitin sulfate have been implicated in cell adhesion to several sites in the III 12-14 domains of HBFN-f (25)(26)(27)(28)(29), suggesting that binding of HBFN-f to cell surface PGs may trigger collagenase induction.…”
Section: Discussionmentioning
confidence: 99%
“…Several sites in the heparin-binding domain that are COOH-terminal to the central cell-binding domain also interact with the cell surface. Several peptides from domain III 12-14 support cell attachment with varying affinities (24)(25)(26)(27)(28)(29). The IIICS, or the variable (V) region, contains the integrin-binding sites, CS-1 and CS-5 (30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Alternatively, MMP induction by COOH-HBFNf-stimulated RSF may involve other mechanisms. Because cell surface heparan sulfate and chondroitin sulfate are implicated in cell adhesion to several sites in the III12 to 14 domains of COOH-HBFN-f (Drake et al, 1992;Iida et al, 1992), binding of COOH-HBFN-f with cell surface proteoglycans may contribute to MMP induction, which is under investigation.…”
Section: Yasuda Et Almentioning
confidence: 99%